2010
DOI: 10.1002/app.32255
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated crystallization and self‐nucleation behavior of poly(ethylene oxide) in its miscible blends with poly(3‐hydroxybutyrate)

Abstract: ABSTRACT:The fractionated crystallization and selfnucleation behavior of poly(ethylene oxide) (PEO) component in the miscible PEO/poly(3-hydroxybutyrate) (PHB) binary blends were investigated using differential scanning calorimetry (DSC) and small-angle X-ray diffraction (SAXS) under different crystallization conditions. The distribution of PEO component in the PEO/PHB blend greatly influences its fractionated crystallization behavior. The active heterogeneities, on which the semicrystalline components in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…PEF self‐nucleation behavior was investigated by FSC measurements using an experimental approach which was first described by Fillon et al for DSC analysis and which was widely employed afterward . The self‐nucleation technique proposed consists in heating a previously crystallized sample to a certain temperature close to the polymer melting point, namely the self‐nucleation temperature, T s .…”
Section: Resultsmentioning
confidence: 99%
“…PEF self‐nucleation behavior was investigated by FSC measurements using an experimental approach which was first described by Fillon et al for DSC analysis and which was widely employed afterward . The self‐nucleation technique proposed consists in heating a previously crystallized sample to a certain temperature close to the polymer melting point, namely the self‐nucleation temperature, T s .…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have found that the binary miscible crystalline/crystalline polymers show the confined and fractional crystallization behavior because of the phase separation and segregation in different length scales during crystallization process. These crystalline/crystalline polymer blends included poly(ethylene terephthalate) (PET)/poly(butylene terephthalate) (PBT) [75], poly(3-hydroxybutyrate) (PHB)/poly(ethylene oxide) (PEO) [76,77], poly(vinylidene fluoride) (PVDF)/poly(butylene adipate) (PBA) [78][79][80], PVDF/poly(butylene succinate-co-butylene adipate) (PBSA) [81], PVDF/PHB [82], PVDF/poly(butylene succinate) (PBS) [83][84][85], PBS/PEO [86][87][88][89][90][91][92], PBS/PBA [93,94], poly(butylene adipate-co-butylene succinate) (PBAS)/PEO [95], poly(ethylene succinate) (PES)/PEO [96], PLLA/poly(oxymethylene) [97,98], and so on. Expect for the miscible blends with one or two crystalline homopolymers, the miscible copolymer/copolymer blends having crystalline components or blocks could also show the confined crystallization behavior [99,100].…”
Section: Crystalline Morphology Of Polymers Confined In Miscible Blendsmentioning
confidence: 99%
“…It is interesting that the polymer particle had a higher T c than the corresponding bulk sample; this was indicative of the faster crystallization of the former. This contradicted the general theory of confined crystallization, in which the crystallization rate of a polymer confined in a nanometer‐scaled environment is usually decreased because of the difficulty of heterogeneous nucleation …”
Section: Resultsmentioning
confidence: 90%